Curvularia alcornii Aortic Pseudoaneurysm Following Aortic Valve Replacement: Case Report and Review of the Literature. (3rd November 2021) - Narayanasamy, Shanti; Williams, Adam R; Schell, Wiley A; Moehring, Rebekah W; Alexander, Barbara D; Le, Thuy; Bharadwaj, Ramesh A; McGauvran, Michelle; Schroder, Jacob N; Perfect, John R
Abstract: We report the first case of Curvularia alcornii aortic pseudoaneurysm following bioprosthetic aortic valve replacement in an immunocompetent host. Infection was complicated by septic emboli to multiple organs. Despite aggressive surgical intervention and antifungal therapy, infection progressed. We review the literature on invasive Curvularia infection to inform diagnosis and management.